2001
DOI: 10.1046/j.1570-7458.2001.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of the predatory mites Typhlodromalus manihoti and Typhlodromalus aripo to cassava plants infested by cassava green mite

Abstract: The attraction of the predatory mites, Typhlodromalus manihoti and Typhlodromalus aripo, to the host plant‐spider mite complex, Manihot esculenta–Mononychellus tanajoa, was investigated with a Y‐tube olfactometer. Factors examined included predator starvation period, several combinations of cassava leaf biomass and initial M. tanajoa infestations, M. tanajoa‐damaged leaves with mites and/or their residues removed, M. tanajoa alone, and mechanically damaged cassava leaves. We found that females of T. manihoti a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…1B) revealed a significant response to the former (PROC GLM F = 11.63, df = 7, P = 0.014 (SAS Institute Inc. 1989)). These results are in accordance with those of Sabelis et al (1984) who found that T. urticae in itself is not attractive to P. persimilis; and with those of Gnanvossou et al (2001), who showed that neither of two predatory mites (Typhlodromalus manihoti Moraes and T. aripo DeLeon (Acari: Phytoseiidae)), were attracted to the direct odour of the cassava green mite, Mononychellus tanajoa (Bondar) (Acari: Tetranychidae). Dong and Chant (1986), on the other hand, reported that both adult females and protonymphs of P. persimilis were attracted to adults and webbing odours of adult Tetranychus pacificus (McGregor) (Acari: Tetranychidae) (but not to odours from either prey eggs, larvae or protonymphs).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1B) revealed a significant response to the former (PROC GLM F = 11.63, df = 7, P = 0.014 (SAS Institute Inc. 1989)). These results are in accordance with those of Sabelis et al (1984) who found that T. urticae in itself is not attractive to P. persimilis; and with those of Gnanvossou et al (2001), who showed that neither of two predatory mites (Typhlodromalus manihoti Moraes and T. aripo DeLeon (Acari: Phytoseiidae)), were attracted to the direct odour of the cassava green mite, Mononychellus tanajoa (Bondar) (Acari: Tetranychidae). Dong and Chant (1986), on the other hand, reported that both adult females and protonymphs of P. persimilis were attracted to adults and webbing odours of adult Tetranychus pacificus (McGregor) (Acari: Tetranychidae) (but not to odours from either prey eggs, larvae or protonymphs).…”
Section: Resultssupporting
confidence: 92%
“…faeces, webbing etc.). However, predatory mites have been shown to react to odours emanated directly by tetranychid mites and their associated products (Sabelis et al 1984;Dong and Chant 1986;Gnanvossou et al 2001;Gols et al 2003) and it is therefore possible that also conspecific and heterospecific herbivores posses the ability to react not only to HIPVs but also to such direct odours.…”
Section: Introductionmentioning
confidence: 99%
“…Gnanvossou et al (2001) and Magalhaes et al(2002) found that T. aripo has a high searching ability for CGM, at very low prey densities, which increases its efficiency as a biocontrol agent. Cassava varieties that sustain relatively low CGM population will facilitate biological control by T. aripo at a fast rate.…”
Section: Introductionmentioning
confidence: 98%
“…As a consequence of feeding damage, cassava plants release a blend of volatiles (including MeSA), which has been also found to attract several phytoseiid mites that are predators of M. tanajoa (Janssen et al 1990;Gnanvossou et al 2001). The entomopathogenic fungus N. tanajoae is specific to M. tanajoa (De Moraes and Delalibera 1992;Hountondji et al 2002;Delalibera and Hajek 2004).…”
Section: Introductionmentioning
confidence: 99%